Halal Industry and Islamic Epistemology: Implications for Policy, Ethics, and Global Practices - Abdul Wahab; Arqom Kuswanjono; Ilma Mahdiya (Journal of Islamic Economic Laws, 2026)
The rapid growth of the global halal industry demands an epistemological framework that is rooted in Islamic principles and aligned with international regulations. This study addresses three questions: (1) how Islamic epistemology can be systematically constructed through its ontological foundations and axiological orientations to form a coherent halal industry framework; (2) how Islamic epistemology informs public policy and ethical governance globally; and (3) what is the most effective model for integrating maqasid al-shari‘ah into cross-jurisdictional halal certification and audits. Using a qualitative conceptual research design based on integrative library research and doctrinal analysis of classical Islamic texts, contemporary maqasid literature, and international halal standards, this study develops a Maqasid-Driven Halal Governance Model (MDHGM). Within this framework, ontology clarifies the metaphysical assumptions underpinning halal norms, while axiology specifies the ethical objectives that guide epistemological reasoning and regulatory application. Findings show that embedding Islamic epistemology into regulatory practices enhances traceability, performance, and contextual adaptability. Harmonizing maqasid values with global regulations strengthens trust, interoperability, and sustainability in the halal industry. This study is limited by its conceptual and library-based design, which lacks empirical validation across diverse institutional and regulatory contexts. Future research should empirically test the proposed model across jurisdictions and industry sectors to assess its applicability and robustness.